Learning Obstcle Siswa Dalam Menyelesaikan Soal Konversi Satuan Waktu Kelas III SD Negeri 40 Palembang - Anggraini, Sela; Fuadiah, Nyiayu Fahriza; Sari, Eka Fitri Puspa (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to describe learning obstacles in time unit conversion material which can be seen from 3 (three) aspects, namely ontogenically obstacle, didactical obstacle, and epistemological obstacle. This research uses qualitative methods and instruments in the form of tests, interviews with class III students and teachers and is supported by analyzing lesson plans, analysis of teaching materials and textbooks. The subjects of this research were class III students at SD Negeri 40 Palembang, totaling 22 students and 1 class teacher. The results of this research found learning obstacles experienced by students, namely lack of motivation in learning, lack of interest in learning mathematics which became an ontogeny obstacle, the learning methods used by teachers were inappropriate which became a didactic obstacle, students’ limitations in understanding the material which became an epistemological obstacle.